2009
DOI: 10.1016/j.jue.2009.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Geographic concentration and vertical disintegration: Evidence from China

Abstract: Existing theoretical literature predicts that geographic concentration encourages vertical disintegration of firms. Nevertheless, empirical evidence of this prediction is limited, especially in developing countries. Using data on manufacturing firms from China, this paper documents a positive correlation between geographic concentration and vertical disintegration. Additionally, this paper uses the instrumental variable approach to address the issue of endogeneity and finds that geographic concentration has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
38
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 77 publications
6
38
0
1
Order By: Relevance
“…Both the pooled OLS estimation and the panel …xed-e¤ect estimation show that industrial agglomeration, measured by a …rm's total neighboring employment within the same 4-digit industry and same city, has a positive and statistically signi…cant impact on …rm size. To identify whether industrial agglomeration has a causal impact on …rm size, we use the instrumental variable estimation à la Li and Lu (2009). The instrumental variable estimation results substantiate our early …ndings, showing that industrial agglomeration causes …rms to become large in production scale.…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…Both the pooled OLS estimation and the panel …xed-e¤ect estimation show that industrial agglomeration, measured by a …rm's total neighboring employment within the same 4-digit industry and same city, has a positive and statistically signi…cant impact on …rm size. To identify whether industrial agglomeration has a causal impact on …rm size, we use the instrumental variable estimation à la Li and Lu (2009). The instrumental variable estimation results substantiate our early …ndings, showing that industrial agglomeration causes …rms to become large in production scale.…”
Section: Introductionsupporting
confidence: 60%
“…1 The agglomeration of industrial activities has signi…cant impacts on …rm behavior and …rm performance such as productivity (e.g., Ciccone and Hall, 1996;Henderson, 2003), organization of production processes (e.g., Holmes, 1999;Li and Lu, 2009), and innovation (e.g., Feldman and Audretsch, 1999;Carlino, Chatterjee, and Hunt, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, regions with more active industrial and commercial activities in the pre-Communist era demonstrated stronger inclination and ability to carry out market economy activities in recent decades (e.g., Zhu, 2001;Fu, 2003). And regions with a large population in the Qing Dynasty continue to prosper in the Communist rule era (e.g., Li and Lu, 2009). Clearly, the historical proxy is linked with the current institutions through the persistent components of institutions that were carried over generation after generation.…”
Section: Instrumental Variable Iii: the Distribution Of Domestic Bankmentioning
confidence: 99%
“…See Li and Lu (2009) for a paper about input outsourcing in China. 12 These industries are included in the robustness checks.…”
mentioning
confidence: 99%